Phenolic Compounds, Antioxidants, and Antibacterial Activity of Some Native Medicinal Plants Against Pseudomonas Aeruginosa - Mandana Ahmadi; Nima Bahador; Alireza Khodavandi (Mazandaran University of Medical Sciences, 2022)
Background: Traditional medicines have a wide range of pharmacological properties. Objectives: This work was done to investigate the antimicrobial effect of Thymus vulgaris, Matricaria chamomilla, Melissa officinalis, and Rhus coriaria extracts against clinical isolates of Pseudomonas aeruginosa. Methods: A total of 180 P. aeruginosa clinical isolates were examined. Using the disc diffusion method, MIC and MBC of the methanol and alcohol herbal extracts were measured. Furthermore, microtiter plate assay evaluated biofilm development in the P. aeruginosa isolates. The free radical scavenging activity of the plant extracts against 2,2-diphenyl-1-picrylhydrazyl (DPPH) was determined. Results: Results showed that P. aeruginosa strains were resistant to more than three different classes of antibiotics. Our results demonstrated that the MBC value of ethanol and methanol extracts of thyme was 43.75 mg/mL, and 31.25 mg/mL, respectively. The highest MIC and MBC values were observed for the thyme and Lemon balm had the lowest MIC and MBC values. Our study showed that thyme extract was the most efficient plant extract against P. aeruginosa. The Mean±SD scavenging activity of thyme, chamomile, sumac, and lemon balm was 91.05±1.10, 89.55±0.70, 64.65±1.95, and 80.1±0.30%, respectively Conclusion: These findings may help in reducing our dependence on antibiotics and handling infections of opportunistic pathogens more efficiently. Further studies are required to distinguish the most important phytochemical compounds and estimate their antibiofilm activities and their mechanisms of action.